INJÚRIA RENAL AGUDA EM PACIENTES HIV/AIDS HOSPITALIZADOS - Jackelyne Alves de Medeiros Vilela (2022)
HIV-infected patients are more vulnerable to Acute Kidney Injury (AKI). The aim of this study was to estimate the incidence and analyze factors associated with Acute Kidney Injury (AKI) in hospitalized HIV/AIDS patients, as well as their impact on the length of hospital stay. The study was carried out at the Maria Aparecida Pedrossian University Hospital, from November 2020 to April 2022. Patients who were diagnosed with HIV/AIDS during hospitalization and who were not on ART were prospectively included. AKI was diagnosed and classified according to the Kidney Disease Improving: Global Outcomes (KDIGO) criteria. Sixty-three patients were included. The most of them were men (n=47; 74.6%) and the median age and CD4+ count were 42 years [Q1;Q3 29; 53] and 40.5 [Q1; Q3 25.0; 104], respectively. Almost all (n= 59; 93.7%) had some opportunistic disease, the most frequent being: tuberculosis (n=25; 39.7%), neurotoxoplasmosis (n=16; 25.4%), pneumocystosis (n= 15; 23.8%), visceral leishmaniasis and cryptococcosis (n=10; 15.9%). The cumulative incidence of AKI was 65.1% (95% CI). The median time to AKI was 5 days [Q1; Q3 2; 14] after admission. Variables associated with AKI were: low CD4+ cell count, cryptococcosis, use of amphotericin B, use of vasopressor drugs and need for ventilatory support. Fifteen (36.6%) achieved the highest AKI classification (KDIGO 3) and the main causes were sepsis and nephrotoxicity. Eight patients (53.3%) underwent hemodialysis. Baseline CD4+ cell count was a variable that showed association with AKI (p=0.032). Patients with AKI were hospitalized longer than those without AKI, with a mean of 16.8 days (SD 10.7) VS 32.4 days (SD 12.8) (p<0.001). Amphotericin B use was independently associated with the development of AKI during hospitalization. The results showed that the incidence of AKI in hospitalized patients with HIV/AIDS is high and that those with AKI have twice the hospitalization time. Measures to prevent opportunistic diseases, especially those that require the use of amphotericin B deoxycholate, such cryptococcosis, can impact on the reduction of AKI in hospitalized HIV/AIDS patients. Keywords: AIDS. Acute kidney injury. CD4+. Hospitalization. Nephrotoxicity.